1998
DOI: 10.1063/1.122772
|View full text |Cite
|
Sign up to set email alerts
|

Metal–insulator transition in SrRuO3 induced by ion irradiation

Abstract: We have studied the effect of He ϩ irradiation on the electrical resistivity and Curie temperature of ferromagnetic SrRuO 3 thin films. An evolution from metallic to insulating behavior is observed when He ϩ ion fluence is increased, suggesting a metal-insulator transition. Damage by ion irradiation produces a strong decrease of the Curie temperature. On the other hand, no significant change in T c ͑ϳ160 K͒ takes place in fresh samples grown at different substrate temperatures. We discuss the possible correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 15 publications
2
20
1
Order By: Relevance
“…The epitaxial (001) SRO thin film exhibited the highest electrical conductivity of 2:4 Â 10 5 SÁm À1 at room temperature. It is reported that an expansion of c-axis induced by ion irradiation would cause the change of conduction behavior from metallic to semi-conductor like accompanying the decrease in T C from 160 K to 110 K. 20) Although the SRO thin films obtained in the present study showed the expansion of c-axis, no change of conduction behavior was observed. 4,[11][12][13][14]16,19,24) However, the T C of epitaxial SRO thin films were 10 K lower than that of single-crystals, ranging from 160 to 170 K. 5,27,28) This might be affected by lattice stress in the films.…”
Section: Methodscontrasting
confidence: 46%
See 1 more Smart Citation
“…The epitaxial (001) SRO thin film exhibited the highest electrical conductivity of 2:4 Â 10 5 SÁm À1 at room temperature. It is reported that an expansion of c-axis induced by ion irradiation would cause the change of conduction behavior from metallic to semi-conductor like accompanying the decrease in T C from 160 K to 110 K. 20) Although the SRO thin films obtained in the present study showed the expansion of c-axis, no change of conduction behavior was observed. 4,[11][12][13][14]16,19,24) However, the T C of epitaxial SRO thin films were 10 K lower than that of single-crystals, ranging from 160 to 170 K. 5,27,28) This might be affected by lattice stress in the films.…”
Section: Methodscontrasting
confidence: 46%
“…[6][7][8][9][10] Since SRO has a good chemical stability and lattice matching to wide ranged oxides, epitaxial SRO thin films has been prepared on various single-crystal substrates such as SrTiO 3 (STO), 4,[11][12][13][14][15][16][17] LaAlO 3 , 18,19) MgO, 20) YSZ 21) and Si. 22) STO is particularly advantageous in preparing high quality epitaxial SRO thin films because the lattice parameter of STO (a ¼ 0:391 nm) is almost the same as that of SRO (a ¼ 0:393 nm).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing irradiation doses resulted in an enlargement of the pseudocubic c-lattice parameter. 11 Scanning electron microscopy observations revealed a granular structure with an average grain size of 0.5 m. Surface topography and grain size were not affected by irradiation. Transmission electron microscopy experiments performed using cross-section geometry before and after irradiation showed that the intergrain structure was not changed due to the irradiation process either.…”
Section: Resultsmentioning
confidence: 95%
“…11 Interestingly enough, ion damage destroys ferromagnetism, while for virgin films grown on the same substrate with different deposition conditions the Curie temperature remains essentially unchanged (T c ϳ160 K). In this paper we present a study of the low-temperature resistivity of poorly conducting thin-film samples of SrRuO 3 obtained by ion irradiation, and virgin samples displaying a low-temperature upturn of the resistivity.…”
Section: Introductionmentioning
confidence: 99%
“…1) Since SRO has a pseudo-cubic perovskite structure similar to ferroelectric PbZr x Ti 1Àx O 3 (PZT) and BaSr x Ti 1Àx O 3 (BST) materials, SRO thin film would provide good bottom electrodes for ferroelectric devices with a layered structure, where well-coherent or epitaxial film with a flat surface texture is required. [2][3][4] SRO thin films have been prepared by sputtering, 3,[5][6][7] metal-organic chemical vapor deposition (MOCVD) 7,8) and laser ablation (pulsed laser deposition). [9][10][11][12] It is known that sputtering often causes a significant difference of composition between targets and films and that MOCVD requires subtle control of the composition due to the difference of chemical stability between alkaline-earth and noble metal precursors.…”
Section: Introductionmentioning
confidence: 99%